2010
DOI: 10.1002/art.27567
|View full text |Cite
|
Sign up to set email alerts
|

Trex‐1 deficiency in rheumatoid arthritis synovial fibroblasts

Abstract: Objective. To explore whether the increased expression of long interspersed nuclear element 1 (LINE-1; L1) messenger RNA (mRNA) and protein in rheumatoid arthritis synovial fibroblasts (RASFs) is associated with decreased expression of Trex-1, an exonuclease involved in the metabolization of L1 DNA: RNA hybrids.Methods. Chromatin immunoprecipitation was used to detect L1-related p40 protein (L1-ORF1p) binding sequences in RASFs. Luciferase activity was measured in the synovial fibroblasts following cotransfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Moreover, single-stranded DNA derived from endogenous retroelements accumulated in Trex1 -deficient cells, and Trex1 overexpression blocked RTP of L1 (Stetson et al, 2008). Consistent with these experimental data, Trex1 activity was reduced in the synovial fibroblasts of rheumatoid arthritis patients (Neidhart et al, 2010). These observations suggest that RTP-induced production of DNA derived from endogenous retroelements is a potential molecular mechanism for the development of autoimmune disorders.…”
Section: L1-rtp Is Linked To the Development Of Various Diseasessupporting
confidence: 67%
“…Moreover, single-stranded DNA derived from endogenous retroelements accumulated in Trex1 -deficient cells, and Trex1 overexpression blocked RTP of L1 (Stetson et al, 2008). Consistent with these experimental data, Trex1 activity was reduced in the synovial fibroblasts of rheumatoid arthritis patients (Neidhart et al, 2010). These observations suggest that RTP-induced production of DNA derived from endogenous retroelements is a potential molecular mechanism for the development of autoimmune disorders.…”
Section: L1-rtp Is Linked To the Development Of Various Diseasessupporting
confidence: 67%
“…This is interesting in light of the fact that LINE-1 is known to be deregulated in RASF [3] and the PIWIL/piRNA system is believed to have a main function in silencing of transponsable elements. [6] However there is another system to control LINE-1 expression, namely TREX-1 which has been found to be deficient in RASF,[27] suggesting a redundancy in LINE-1 silencing mechanisms with apparently less importance of the PIWIL/piRNA system in RASF.…”
Section: Discussionmentioning
confidence: 99%
“…Second, alternative evidence shows that ssDNA originates from the replication of endogenous retroelements being accumulated in Trex1-deficient mice (13). In fact, it has been found that Trex1 also neutralizes part of the function of endogenous retroelements in synovial fibroblasts, which in consequence leads to rheumatoid arthritis when Trex1 is not present (14). The IFN-ab production, which contributes to the above-mentioned, has been shown to be dependent on stimulator of IFN genes (STING) pathway (15).…”
mentioning
confidence: 99%